Zonificação ambiental do estado do Maranhão utilizando os geossistemas como categoria geográfica de análise - MARQUES, Valter José (Universidade Federal do Pará, 2017)
The state of Maranhão possesses 331.937 square kilometers; coated to the west by dense ombrophylous forests and to the east for cerrado and forests of babaçu, in transition for the biome caatinga. In the latitudinal dimension, are distinguished two large bays: coastal and continental, separated by a structural and step-W/NW. To this geographical diversity correspond geological, geomorphological, climatic and soil nuances, which result in different occupations and uses of geographic space. Even here, the territorial planning has supported in the political-administrative division and in actual or potential uses of the natural environment. The ambient boardings are based on the thematic striking on the ecological dimension and/or on the geomorphological compartments. In the present study, it was opted to the zonification under the systemic perspective of the geossystem-territory-landscape method, wich embraces the the biases physical, biotic and sociocultural. The discrimination of geossystems and the search for its origins had allowed to greater clarification on the connection and tectonic evolution of the Brazilian continental platform, on account of the continental drift, that separated Brazil from Africa. In the local regional/locale/, the 12 geossystems mapped behave as “crustals paving-tiles”, put into motion for forces of the internal dynamics of the Earth. The delineation of the geossystemic units is consonante with the one of the gravimetrical anomalies and the limits of the hydrographic basins. Biotic and physical themes are reflected on the geossystemic units, as the uses of land, and cultural aspects are, showing their integrated nature. Of this form, the zonification, on the basis of geossystems, makes possible the territorial management, through its ambiental, hydric, ecological and economic biases. As retrospective of the territorialities, implanted throughout the history of the Maranhão, the fact ascends of that they had as force-motor the production of substances cousins for global markets. These contingencies, associates with the non- inclusive politics involving populations on the global businesses resulted in significant social exclusion. Finally, an assay directed to the formularization of alternative scenes, under the optics of the sustainable development, advocates for new aimings marked out with buoys in complete a territorial vision, that over all prioritizes the technological quality of the human resources and innovations with respect to the energy matrix, infrastructure, verticalization of local productive chains and in the adoption of ambient politics regarding nature conservation and preservation of environmental services.